2010
DOI: 10.1074/jbc.m110.118406
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid-metabolizing Cytochrome P450 Enzymes Are Targets of ω-3 Fatty Acids*

Abstract: Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) protect against cardiovascular disease by largely unknown mechanisms. We tested the hypothesis that EPA and DHA may compete with arachidonic acid (AA) for the conversion by cytochrome P450 (CYP) enzymes, resulting in the formation of alternative, physiologically active, metabolites. Renal and hepatic microsomes, as well as various CYP isoforms, displayed equal or elevated activities when metabolizing EPA or DHA instead of AA. CYP2C/2J isoforms converti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
340
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 333 publications
(366 citation statements)
references
References 78 publications
23
340
1
2
Order By: Relevance
“…For detection and quantification of the metabolites, an online radio flow detector (LB 509; Berthold) was used. Authentic standard compounds were prepared and used as described previously [26,27]. The AA and EPA hydroxylase activities were derived from the sum of 19-/20-HETE (19-/20-hydroxyeicosatetraenoic acid) and 19-/20-HEPE (19-/20-hydroxyeicosapentaenoic acid), respectively, and total AA and EPA epoxygenase activities as the sum of all detectable EETs (epoxyeicosatrienoic acids) and EEQs, respectively.…”
Section: Analysis Of the Metabolite Profilesmentioning
confidence: 99%
“…For detection and quantification of the metabolites, an online radio flow detector (LB 509; Berthold) was used. Authentic standard compounds were prepared and used as described previously [26,27]. The AA and EPA hydroxylase activities were derived from the sum of 19-/20-HETE (19-/20-hydroxyeicosatetraenoic acid) and 19-/20-HEPE (19-/20-hydroxyeicosapentaenoic acid), respectively, and total AA and EPA epoxygenase activities as the sum of all detectable EETs (epoxyeicosatrienoic acids) and EEQs, respectively.…”
Section: Analysis Of the Metabolite Profilesmentioning
confidence: 99%
“…Eicosanoids include prostaglandins (PGs), leukotrienes, epoxyeicosatrienoic acids (EETs) and hydroxyeicosatrienoic acids (HETEs) [76]. Docosanoids include docosatrienes, protectins and resolvins [82][83].…”
Section: Fabp7/fatty Acid Mechanisms Controlling Malignant Glioma Migmentioning
confidence: 99%
“…A report from 30 years ago showed that DHA acts as a potent competitive inhibitor of AA metabolism by COX-2 [115]. More recent reports indicate that DHA also inhibits AA metabolism by CYP epoxygenases and hydroxylases [82]. In brain-metastatic melanoma and in a neuroblastoma cell line [116], DHA competition with AA resulted in decreased PGE 2 levels, with COX-2-mediated DHA metabolite PGE 3 significantly decreasing invasion in a dose-dependent manner [46].…”
Section: Docosahexaenoic Acid-related Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzymes of the cytochrome P450 system were found to metabolise AA to epoxyeicosatrienoic acid and hydroxy fatty acids, biologically active compounds with a variety of functions, including vasodilatation, angiogenesis and inflammation resolution, protecting the ischemic myocardium and brain [16][17][18].…”
Section: Introductionmentioning
confidence: 99%